A Comparative Study of Trained and Untrained Science Students’ Attitude Towards Entrepreneurship, Innovation, Training, and Science Studies: Implications for Practical Education - Busagara, Theresia Edward; Mukama, Regina Vicent; Magai, Petro Sauti (Papers in Education and Development, 2024)
This comparative study examines the attitudes of trained and untrained science students in advanced-level secondary schools towards entrepreneurship, innovation, training, and the relevance of science studies. Data were collected from eighty-five advanced-level secondary school students and analysed using descriptive and inferential statistics. In the inferential statistics, a t-test was used to establish the mean differences between the trained and untrained science students on their attitude towards the importance of entrepreneurship, innovation, science studies, and training. The findings revealed that trained students depicted a high attitude towards entrepreneurship (µ=8.72), innovation (µ=8.59), training (µ=8.29), and higher engagement with their science studies (µ=9.10) at a p < 0.05 significance level. The study underscores the importance of promoting scientific, entrepreneurial practices for sustainable scientific development. It also highlights the inadequacy of a formal education curriculum alone, advocating for supplementary entrepreneurial training to effectively translate formal knowledge into solutions for social problems. Keywords: Science students, attitude, entrepreneurship, innovation, education